The Millennium Villages Project: Outcomes Evaluation. Issue 5 (September 2018) - Callister, Lynn Clark
Abstract : The Millennium Villages Project was a visionary 10-year global project in 14 rural sites in 10 sub-Saharan African countries (Ethiopia, Ghana, Kenya, Malawi, Mali, Nigeria, Rwanda, Senegal, Tanzania, and Uganda). Our global health nursing expert, Dr. Callister, explains the recently published results including the significant positive findings for health outcomes based on the Millennium Development Goals.